Combining ability and genetic diversity of extraearly white maize inbreds under stress and nonstress environments - Badu-Apraku, Baffour; Oyekunle, M.; Akinwale, R.; Aderounmu, R.O. (Wiley, 2013)
Maize (Zea mays L.) has the greatest yield potential in savannas of West and Central Africa (WCA). However, production in this agroecology is constrained by low levels of N, drought, and parasitism by striga [Striga hermonthica (Del) Benth.]. Diallel crosses involving 17 extra-early white maize inbreds were evaluated under drought, striga, and optimal environments at three locations in Nigeria for 2 yr. The objectives of this study were to estimate general and specific combining ability for grain yield, classify the inbreds into heterotic groups, and identify inbred testers. Gene action controlling grain yield and most other traits was predominantly nonadditive. TZEEI 14, TZEEI 29, TZEEI 21, and TZEI 13 were the best testers across environments. Four heterotic groups were identified based on the heterotic group’s specific and general combining ability (HSGCA) method and five groups based on microsatellite markers. TZEEI 29 × TZEEI 14 was the second highest yielding and most stable across environments. Fifty-nine alleles with an average of 2.57 alleles per locus were detected among the inbreds. Correlation between genetic distance estimates of parental lines and their F1 hybrid means were not significant for grain yield and most other traits. There was close correspondence between heterotic groups identified by the HSGCA method and microsatellite markers. Extra-early inbreds and hybrids with drought tolerance and striga resistance genes identified should be used to reduce instability of maize yields in WCA.